Thyroid Disorders in Pregnancy: An Exploratory Study - Jyochnamayi Panda; Aparajita Maji; Jayanti Mishra; Magna Manjareeka (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Thyroid disorders, mostly hypothyroidism, being one of the common diseases during pregnancy, if untreated, affect the neuro-psycho development of neonates. Many factors influence thyroid function tests in pregnancy; ethnic variations or different environmental conditions being one of them. Aim: This study was done to find the prevalence of overt hypothyroidism, subclinical hypothyroidism, overt hyperthyroidism and subclinical hyperthyroidism in the pregnant women in all trimesters. Materials and Methods: The present cross-sectional study was carried out by the Department of Obstetrics and Gynaecology and the Department of Physiology over a period of one year. Pregnant women who consented; with uncomplicated singleton pregnancy attending the antenatal check up for first time at antenatal OPD were included for the study. Blood samples for the estimation of FT4 and TSH were collected during a specific time period of the day. Serum FT4 and TSH estimation were done using an electro-chemiluminescent immunoassay technique. Results: Amongst the total 505 enrolled pregnant ladies 428 were included in the study. There were (n=278, 65.0%), (n=146, 34.1%) and (n=4, 0.9%) women in their first trimester, second trimester and third trimester respectively. With TSH cut off at 2.5 mIU/L, prevalence of subclinical hypothyroidism was (n=159, 37.15%) and overt hypothyroidism was (n=48, 11.21%). Prevalence of subclinical hypothyroidism was (n=13, 3.04%) when TSH cut off 4.5 mIU/L was considered. There was no significant difference in prevalence of subclinical hypothyroidism or overt hypothyroidism in pregnant ladies in different trimesters. Prevalence of subclinical hypothyroidism and overt hypothyroidism was lesser in women in primi gravida than women in multi gravida. There were no women with subclinical hyperthyroidism or overt hyperthyroidism. Conclusion: Hypothyroidism is more prevalent among the thyroid disorders during pregnancy. Prevalence of subclinical and overt hypothyroidism is more in multiparous pregnant women, irrespective of their trimesters.